Broadcasting revenues and media value in European football - Pedro Garcia del Barrio; Francesc Pujol (Kiel Institute for the World Economy (IfW), 2016)
Sport talent and popularity are major assets on which some businesses develop their economic activities. Professional football is one of the markets that, being among the principal industries of entertainment, depend on the skills of players. This paper uses media value ratings to appraise the sport talent and potential economic contribution of players and teams in European football. The empirical analysis shows also that sport performance and attainments are keystone elements to procure visibility in the media and to attract potential revenues. The goal of this paper is twofold. Firstly, it investigates the factors that enhance exposure and media value of professional football clubs. The media value status and popularity are mainly driven by past and current sport performance. Besides, our media value indexes for teams and leagues, which are derived from individual appraisals, inform about their potential capacity to generate income. Secondly, the paper uses media value appraisals to address if they explain some sources of teams' revenues. The paper actually explores to what extent TV rights are in accordance to the share of interest that each club draws from the fans and the media. Among other results, we find a strong empirical relationship between media value scores and either total revenues or broadcasting revenues. The authors' empirical analysis also indicates that the broadcasting revenues in some of the top European domestic leagues were in the past below the level that according to their media value status one might expect.
Keywords: J24; J33; J71; 330; European football; broadcasting revenues; media value; sport talent; productivity